The Role of Moringa oleifera- Ifalmin® Formulation in Regulation of B220+IgM+ and B220+IgG+ in Diabetic Mice - Wahyu Isnia Adharini; Ruri Vivian Nilamsari; Noviana Dwi Lestari; Nashi Widodo; Muhaimin Rifa'i (Journal of Experimental Life Science)
It has been known that the immunoglobulin levels were altered in diabetes mellitus (DM) conditions. This study aimed to evaluate the levels of immunoglobulins in DM mice after the administration of Moringa oleifera-Ifalmin® formulation (MI). Streptozotocin, at a dose of 145 mg.kg-1, was injected intraperitoneally to experimental mice to obtain diabetic mice. The groups were divided into normal mice, diabetic mice without treatment, diabetic mice with metformin treatment (307.5 mg.kg-1 BW), and diabetic mice with MI treatment at dose 1 (M:I= 800 mg.kg-1 BW: 800 mg.kg-1 BW), dose 2 (M:I= 615 mg.kg-1 BW: 615 mg.kg-1 BW), and dose 3 (M:I= 800 mg.kg-1 BW: 615 mg.kg-1 BW). Mice were orally treated by MI for 14 days. Subsequently, the levels of immunoglobulin IgM and IgG were evaluated using flow cytometry analysis. IgM and IgG levels were significantly lower in the DM group than the normal group. These results indicated that DM altered immunoglobulin levels. MI treatment for 14 days significantly increased the number of IgM and IgG at the level equivalent to the normal group and significantly different as compared to the DM group. Based on the results, MI can be used as an immunomodulatory agent in humoral immunity through the precise regulation of IgM and IgG.